Analysis of cerebrospinal fluid in racemose form of neurocysticercosis - Bazan, Rodrigo [UNESP]; Odashima, Newton Satoru; Luvizutto, Gustavo Jose [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Zanini, Marco Antonio [UNESP]; Takayanagui, Osvaldo Massaiti (Assoc Arquivos Neuro- Psiquiatria, 2015)
The present work aimed to evaluate the pattern of CSF alterations in patients diagnosed with neurocysticercosis (NCC) in racemose form. Method: This is a retrospective cohort study of patients with diagnosis of NCC in racemose form. CSF samples from 26 patients were analyzed. After patient-chart analysis was performed descriptive analysis of case studies and comparison between sexes in relation to variables were obtained with CSF by Mann-Whitney and Student's t-tests. Results: The sexes did not differ statistically when compared to pleocytosis in CSF. Eosinophils were present in 31% in samples while the ELISA test presented 80% sensitivity in this case series. Of the patient total, 24 presented a meningitis pattern with Lymphocytic predominance. Conclusion: There was no difference in inflammatory pattern between the sexes, with predominance of lymphocytic meningitis and 80% sensitivity by ELISA test of CSF patients with racemose form of NCC.
Keywords: neurocysticercosis; racemose; cerebrospinal fluid